Parking Control System using IR Sensor - Sudha, R (International Journal of Computer Sciences and Engineering, 2025)
This paper deals with sensing the vehicle in no parking area. It uses IR active sensor to sense the vehicle that stands in front of the sensor for a period of time. It immediately sends an alert message to the driver of the vehicle by means of glowing LED light. If the vehicle is not taken then the alert message is send to the traffic cop and action will be taken on that driver. The advantage of this device is to reduced the traffic in the peak areas, and to create awareness among the people to follow the rules.